Risks in the Processes of Digitalization of Law and Supply Chain Strategy in Economic Relations - Alexey I. Ovchinnikov; Artur G. Kravchenko; Alexey Yu. Mamychev (International Journal of Supply Chain Management, 2019)
One of the main trends in the law development is its digitalization under the supply chain strategies, which is manifested both in the digitalization of legal regulation, legal technologies, legal processes and law enforcement. In the emergence of regulations affecting the issues of the digital economy, electronic state, information security. In this article, the authors assess some risks of digitalization of law through the prism of features of logical operations in legal thinking, analyze the interaction of a number of legal institutions and modern supply chain management systems that undergo radical changes in connection with digitalization.